The velocity, temperature and concentration profiles for triple diffusive Casson fluid flow subjected to the Soret-Dufour parameters - Mohamed Isa, Siti Suzilliana Putri; Balakrishnan, Nanthini; Ismail, Nurul Syuhada; Md. Arifin, Norihan; Md Ali, Fadzilah (Akademia Baru Publishing, 2023)
The triple-diffusive convection with the involvement of non-Newtonian fluid has many applications in the science and technology field, industrial processes, and also in research works. Therefore, the mathematical model of the triple-diffusive convection of Casson fluid by the mathematical approach is investigated. In addition, a mathematical model for the triple-diffusive convection of Casson fluid flow beyond a nonlinear compressing sheet has been formulated and solved by numerical approach, where this is the main objective of this study. This model is subjected to mass transfer and heat transfer, known as Soret and Dufour effect (Soret-Dufour). The Soret effect is occurred when the temperature gradient is produced, whereas the differences in mass cause the Dufour effect. The model is formed by the continuity equation, momentum equation, energy equation, and concentration equations of component 1 and 2, together with the boundary conditions. They have been reduced to ordinary differential equations, and subsequently, they have been implemented in bvp4c programme provided by MATLAB software to get the numerical solutions. The solutions obtained were profiles of velocity, temperature and concentration of both components. Next, the effect of Casson parameter, Soret parameter, and Dufour parameter have been investigated by changing their values of inside the coding in MATLAB and observing the behaviour of the related profiles due to these parameters. The main results from this study were: The velocity of the Casson fluid reduced as the Casson parameter enhanced, increment in both Soret and Dufour parameters caused the temperature to decrease, and the fluid concentration was higher for the increasing Soret number.